Emerging Roles for Long Non-Coding RNAs in Cancer and Neurological Disorders - Niland, Courtney N.; Merry, Callie R.; Khalil, Ahmad M. (Frontiers in Genetics, 2012)
The recent discovery of thousands of large non-coding (lnc)RNAs in the human genome prompted investigation of the potential roles of these molecules in human biology and medicine. Indeed, it is now well documented that many lncRNAs are involved in key biological processes including dosage compensation, genomic imprinting, chromatin regulation, RNA splicing and nuclear organization. It is likely that lncRNAs are also involved in many other biological processes, which are yet to be elucidated. Recently, a number of studies have reported that lncRNAs are deregulated in a number of human diseases, specifically in several cancer types and neurological disorders. Although many of these studies have fallen short of implicating lncRNAs as causative, they suggest a potential role that should be elucidated. In this review, we discuss the current state of knowledge regarding the roles of lncRNAs in cancer and neurological disorders, and suggest potential future directions in this rapidly emerging field.